Long term correlation between cancer and cardiovascular deaths according to various trends in Slovak districts 1994-2003 - Letkovicová, Mária; Zach, Hana; Letkovic, Martin; Celko, Alexander Martin (Central European journal of public health, 2007)
The aim of the article was to point out recorded cardiovascular deaths did not copy the real number of cardiovascular deaths, but may also include other causes of deaths. We evaluated all death notifications reported to the Statistical Office of the Slovak republic during the 10-year period, that is 519,680 cases in total. We analysed the year of death, location of death and the cause of death. The causes of deaths were split into three groups: cancer deaths, cardiovascular deaths (CVD) and other deaths. We used the fuzzy c cluster analysis and the basic epidemiological and statistical methods for the evaluation. We uncovered some Slovak districts had long-term higher mortality (Lucenec, Rimavská Sobota, Roznava, Trebisov and Krupina), as well as the other districts having the long-term lower mortality (Bratislava, Kosice, almost all Zilina region, Poprad, Spisská Nová Ves and Dunajská Streda). The cancer and cardiovascular deaths significantly correlated in terms of the Slovak districts. Evaluating the mutual causes of death proportion we identified two groups of Slovak districts; the first group of districts showing higher CVD deaths had lower cancer and other deaths, the second having higher proportion of cancer and other deaths reached the lower CVD deaths. It seems deaths have the similar pattern throughout the whole country, and the numerical differences are probably given only by the quality and the quantity of the death certification.
Keywords: Neoplasms; kardiovaskulární nemoci; shluková analýza; Slovakia; Mortality; lidé; úmrtní listy; časové faktory; Time Factors; Humans; Cluster Analysis; mortalita; Death Certificates; Cardiovascular Diseases; nádory; Slovenská republika